GENETIC AND FUNCTIONAL FACTORS IN THE DEVELOPMENT OF COGNITIVE IMPAIRMENT IN HYPERTENSION: A PROSPECTIVE STUDY - Yu. V. Zhitkova; A. A. Gasparyan; D. R. Khasanova; N. R. Khasanov; V. N. Oslopov (Неврология, нейропсихиатрия, психосоматика)
Objective: to provide a dynamic assessment of cognitive functions in hypertensive patients in relation to the cerebral perfusion reserve and passive transmembrane ion transport velocity.Patients and methods. The investigation enrolled 79 hypertensive patients (the mean age at the start of examination was 54 years), including 44 women (mean age, 58±16.2 years) and 35 men (mean age, 60±9.8 years). During a screening, the mean duration of hypertension was more than 5 years in 60% of the patients and less than 5 years in 40%. 55% of the patients had adequate antihypertensive therapy and normal blood pressure (BP) (<140/90 mm Hg), 45% were not on this therapy and they failed to achieve normal BP. The investigators evaluated a variety of factors, such as gender, age, BP, duration of hypertension, indicators of cerebrovascular reactivity (CVR), and levels of passive transmembrane ion transport, by using a model of Na+-Li+  countertransport (NLCT)  in the erythrocyte membrane as an example.Results. Some risk factors were ascertained to influence cognitive functions in hypertension, but to a greater extent on CVR values in different vascular beds. A correlation was found between CVR and genetically determined NLCT velocity.Conclusion. The indicators CVR and NLCT may be used as predictors for the development and progression of vascular cognitive impairment.